In vivo and ex vivo assessment of bladder hyper-permeability and using molecular targeted magnetic resonance imaging to detect claudin-2 in a mouse model for interstitial cystitis - Smith, Nataliya; Saunders, Debra; Lerner, Megan; Zalles, Michelle; Mamedova, Nadezda; Cheong, Daniel; Mohammadi, Ehsan; Yuan, Tian; Luo, Yi; Hurst, Robert E.; Greenwood-Van Meerveld, Beverley; Towner, Rheal A. (PloS one, 2020)
To determine if the URO-MCP-1 mouse model for bladder IC/BPS is associated with in vivo bladder hyper-permeability, as measured by contrast-enhanced MRI (CE-MRI), and assess whether molecular-targeted MRI (mt-MRI) can visualize in vivo claudin-2 expression as a result of bladder hyper-permeability. Interstitial cystitis/bladder pain syndrome (IC/BPS) is a chronic, painful condition of the bladder that affects primarily women. It is known that permeability plays a substantial role in IC/BPS. Claudins are tight junction membrane proteins that are expressed in epithelia and endothelia and form paracellular barriers and pores that determine tight junction permeability. Claudin-2 is a molecular marker that is associated with increased hyperpermeability in the urothelium. CE-MRI was used to measure bladder hyper-permeability in the URO-MCP-1 mice. A claudin-2-specific mt-MRI probe was used to assess in vivo levels of claudin-2. The mt-MRI probe consists of an antibody against claudin-2 conjugated to albumin that had Gd-DTPA (gadolinium diethylenetriamine pentaacetate) and biotin attached. Verification of the presence of the mt-MRI probe was done by targeting the biotin moiety for the probe with streptavidin-horse radish peroxidase (SA-HRP). Trans-epithelial electrical resistance (TEER) was also used to assess bladder permeability. The URO-MCP-1 mouse model for IC/BPS was found to have a significant increase in bladder permeability, following liposaccharide (LPS) exposure, compared to saline-treated controls. mt-MRI- and histologically-detectable levels of the claudin-2 probe were found to increase with LPS -induced bladder urothelial hyper-permeability in the URO-MCP-1 IC mouse model. Levels of protein expression for claudin-2 were confirmed with immunohistochemistry and immunofluorescence imaging. Claudin-2 was also found to highly co-localize with zonula occlidens-1 (ZO-1), a tight junction protein. The combination of CE-MRI and TEER approaches were able to demonstrate hyper-permeability, a known feature associated with some IC/BPS patients, in the LPS-exposed URO-MCP-1 mouse model. This MRI approach could be clinically translated to establish which IC/BPS patients have bladder hyper-permeability and help determine therapeutic options. In addition, the in vivo molecular-targeted imaging approach can provide invaluable information to enhance our understanding associated with bladder urothelium hyper-permeability in IC/BPS patients, and perhaps be used to assist in developing further therapeutic strategies.